Perlindungan Hukum terhadap Tenaga Kerja pada Usaha Dagang (UD) Sari Yasa di Denpasar - Dewa Ayu Warta Meilaningsih; I Nyoman Gede Sugiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2022)
Business Trading (UD) is a business entity that is run independently by one person only and does not require a partner in doing business. Sari Yasa Trading Company or Trading Company (UD) located in Denpasar. Such as employees or workers who are dishonest and even commit acts against the law in helping carry out business activities and the legal protection provided by a company to its employees or workers considering that the Trading Company or Trading Business (UD) has not been explicitly regulated in the laws and regulations. This study aims to reveal the form of legal protection for workers at the Sari Yasa Trading Business (UD) in Denpasar. The type of research used in this research is empirical legal research with a sociology of law approach that studies the reciprocal relationship between law and other social phenomena. The source of data in this study is primary data and secondary data. The data in this study were processed using qualitative analysis, where the data obtained were presented in a descriptive analysis. The results of this study indicate that because the Trading Company (UD) is not a legal entity, it is therefore full of civil and criminal responsibility for the company's employees. The form of legal protection is to make a work agreement in which the substance has been adjusted to the applicable laws and regulations.